Effects of Mechanical and Enzymatic Pretreatments on Extraction of Polyphenols from Blackberry Fruits. Issue 5 (1st June 2015) - Soto, Marvin; Acosta, Oscar; Vaillant, Fabrice; Pérez, Ana
Abstract: This study evaluated the effects of mechanical and enzymatic pretreatments on the extraction of anthocyanins and ellagitannins from blackberries. Continuous pressing yielded significantly higher turbidity values and content of anthocyanins and ellagitannins ( P  < 0.05) compared with discontinuous pressing. The use of enzymatic pretreatment also significantly increased the extraction of polyphenolic compounds ( P  < 0.05), in particular that of total ellagitannins, on average from 437 to 982 mg ellagic acid equivalents/100 g (dry basis) when using discontinuous pressing. When microfiltration was used, the content of ellagitannins and anthocyanins was found to be similar in both feed and permeate when discontinuous press was used to extract the juice, but a significant decrease of 34% (dry basis) was found in the concentration of ellagitannins when continuous pressing was used ( P  < 0.05). These results should be useful for future efforts to increase the extraction of polyphenolic compounds from fruits and vegetables. Practical Applications: Blackberries have high contents of potentially bioactive polyphenolic compounds, mainly anthocyanins and ellagitannins. Therefore, processes must be optimized not only to obtain large amounts of juice from this fruit, but also to efficiently extract the compounds of interest. The methodology and results presented in this study should be beneficial for processors that aim to increase the recovery of potentially bioactive polyphenolic compounds from fruit using mechanical and enzymatic pretreatments. Furthermore, this study evaluated the potential of cross‐flow microfiltration as a viable operation for cold stabilization of blackberry juice, while obtaining acceptable permeate flux and membrane retention of the compounds of interest. It is envisioned that this technology could be used in the same manner to ensure the microbiological stability of polyphenolic‐enriched fruit juices and extracts.